2020
DOI: 10.1002/cne.25061
|View full text |Cite
|
Sign up to set email alerts
|

Projections of ipRGCs and conventional RGCs to retinorecipient brain nuclei

Abstract: Retinal ganglion cells (RGCs), the output neurons of the retina, allow us to perceive our visual environment. RGCs respond to rod/cone input through the retinal circuitry, however, a small population of RGCs are in addition intrinsically photosensitive (ipRGCs) and project to unique targets in the brain to modulate a broad range of subconscious visual behaviors such as pupil constriction and circadian photoentrainment. Despite the discovery of ipRGCs nearly two decades ago, there is still little information ab… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
34
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 44 publications
3
34
0
Order By: Relevance
“…Traditionally, the vLGN was thought to be involved in circadian-related phenomena by virtue of the fact that it receives input from intrinsically photosensitive ''melanopsin'' RGCs (M1 ipRGCs; Harrington, 1997;Berson et al, 2002;Hattar et al, 2006;Chen et al, 2011). However, we and others have observed that the vLGN receives diverse types of retinal inputs in addition to input from M1 ipRGCs (Figure S8;Osterhout et al, 2011;Dhande et al, 2015;Sonoda et al, 2020;Beier et al, 2021). Recent work points to a role for the vLGN in light-mediated effects on depression and spatial memory-processes that occur on the timescale of days (Huang et al, 2019(Huang et al, , 2021.…”
Section: Discussionmentioning
confidence: 92%
“…Traditionally, the vLGN was thought to be involved in circadian-related phenomena by virtue of the fact that it receives input from intrinsically photosensitive ''melanopsin'' RGCs (M1 ipRGCs; Harrington, 1997;Berson et al, 2002;Hattar et al, 2006;Chen et al, 2011). However, we and others have observed that the vLGN receives diverse types of retinal inputs in addition to input from M1 ipRGCs (Figure S8;Osterhout et al, 2011;Dhande et al, 2015;Sonoda et al, 2020;Beier et al, 2021). Recent work points to a role for the vLGN in light-mediated effects on depression and spatial memory-processes that occur on the timescale of days (Huang et al, 2019(Huang et al, , 2021.…”
Section: Discussionmentioning
confidence: 92%
“…However, optogenetic stimulation of Chronos-expressing slices at the beginning of the projected night was potent to selectively delay activity peak (by ~3 -4.5 h) of the two compartments of VLG, without entraining the IGL. As the VLGm is generally not retinorecipient, or very sparsely innervated by the retina compared to the VLGl (Harrington, 1997;Beier et al, 2020), the phase shift in the VLGm is most likely to be transmitted via the VLGl. This is not surprising, as these two parts of VLG were demonstrated to stay in a strong reciprocal connection (Harrington, 1997;Govindaiah & Cox, 2009;Monavarfeshani et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Circadian rhythms on the molecular level are reflected in the daytime rise in the electrical activity of the SCN neurons followed by their nocturnal silencing (Belle et al, 2009;Colwell, 2011). Additionally, the SCN is best known for its photoentrainability, as it receives a dense innervation from the retinal ganglion cells (heavily from these synthesising a 'circadian photopigment' melanopsin) and responds to ambient light by both neurophysiological excitation and phase shifts in clock gene expression (Beier et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the outer retina, six subtypes of ipRGCs (M1 to M6) can be distinguished, each with unique morphological, functional and physiological properties projecting to different targets in the brain [24][25][26][27][28][29][30][31]. The M1-subtype of the ipRGCs directly innervates specific regions of the suprachiasmatic nucleus (SCN) and olivary pretectal nucleus (OPN) to modulate the non-image-forming mechanism involving the circadian photoentrainment and temporal pupil light constriction [15,18,[32][33][34][35][36][37]. In the inner retina, M1-ipRGC dendrites stratify in the outermost sublamina of the inner plexiform layer (IPL), receiving extrinsic synaptic input from rods, L + M-on and inhibitory S-cone signals [26,28,[38][39][40][41][42][43][44][45][46].…”
Section: Introductionmentioning
confidence: 99%